Labour Relations Trends, Retrospect and Prospect - Cholette, Gaston (Relations industrielles / Industrial Relations, 1960)
The article reviews the book, "Labour Relations Trends, Retrospect and Prospect," published by the Industrial Relations Centre, McGill University.